Slag fragments in heavy mineral concentrates from Bakri Area, Johor - Wan Fuad Wan Hassan, (Universiti Kebangsaan Malaysia, 2001)
This article describes the occurrence of slag fragments from the Bakri area, Johor. The slag occurring as traces in forms of minute spheres, tubes, rods and angular fragments were recovered together with heavy mineral fractions from stream sediments and old mine collections. Polished section study of the slag shows the presence of magnetite mineral and some tin metal surrounded by glassy matrix. Magnetite, the main phase, has textures ranging from euhedral to angular grains and skeletal growth. The skeletal growth texture and shapes of the slag grains such as rods indicate sudden cooling by being poured out from a melt, as is being carried out in a smelting plant. The presence of these slag traces suggest that tin smelting on a small scale was carried out in the vicinity of the present Bakri town by the old generation tin miners, possibly before the coming of the British to Malaya